The Academic Evolution and Research Hotspots of Han Pictorial Stone Studies in China : A Bibliometric Analysis Based on CiteSpace - RONGMING YANG; Qingfeng ZHANG (International Journal of Advanced Culture Technology(IJACT), 2025)
This study aims to explore the academic evolution and research hotspots of Han pictorial stone studies in China, with the goal of providing a systematic understanding of its developmental trajectory and offering strategic insights for future research. Employing bibliometric analysis and knowledge mapping techniques, this research uses CiteSpace software to analyze literature related to Han pictorial stones published from 1954 to 2024 in the CNKI database. The analysis includes publication trends, core authors, research institutions, and keyword clustering, revealing the historical stages and thematic shifts in this field. The results identify four distinct development stages—incipient, growth, rapid growth, and fluctuating growth—during which research interests evolved from basic archaeological excavation to encompass artistic interpretation, symbolic meaning, and digital preservation. Notably, recent studies demonstrate increasing interdisciplinary integration and the use of digital technology in cultural heritage conservation. Despite these advancements, challenges such as limited methodological diversity, weak cross-regional collaboration, and fragmented resources persist. This study contributes to the field by proposing a data-driven, visualized research approach that integrates bibliometric tools with digital humanities perspectives. The findings not only highlight the current landscape of Han pictorial stone research but also emphasize the need for interdisciplinary cooperation and the development of open-access research platforms. This structured analysis is expected to serve as a reference framework for scholars and heritage professionals working to advance the study and preservation of Han pictorial stones.